Hydrophilic Domains of Scaffolding Protein CbpA Promote Glycosyl Hydrolase Activity and Localization of Cellulosomes to the Cell Surface of Clostridium cellulovorans - Kosugi, Akihiko (American Society for Microbiology, 2004)
CbpA, the scaffolding protein of Clostridium cellulovorans cellulosomes, possesses one family 3 cellulose binding domain, nine cohesin domains, and four hydrophilic domains (HLDs). Among the three types of domains, the function of the HLDs is still unknown. We proposed previously that the HLDs of CbpA play a role in attaching the cellulosome to the cell surface, since they showed some homology to the surface layer homology domains of EngE. Several recombinant proteins with HLDs (rHLDs) and recombinant EngE (rEngE) were examined to determine their binding to the C. cellulovorans cell wall fraction. Tandemly linked rHLDs showed higher affinity for the cell wall than individual rHLDs showed. EngE was shown to have a higher affinity for cell walls than rHLDs have. C. cellulovorans native cellulosomes were found to have higher affinity for cell walls than rHLDs have. When immunoblot analysis was carried out with the native cellulosome fraction bound to cell wall fragments, the presence of EngE was also confirmed, suggesting that the mechanism anchoring CbpA to the C. cellulovorans cell surface was mediated through EngE and that the HLDs play a secondary role in the attachment of the cellulosome to the cell surface. During a study of the role of HLDs on cellulose degradation, the mini-cellulosome complexes with HLDs degraded cellulose more efficiently than complexes without HLDs degraded cellulose. The rHLDs also showed binding affinity for crystalline cellulose and carboxymethyl cellulose. These results suggest that the CbpA HLDs play a major role and a minor role in C. cellulovorans cellulosomes. The primary role increases cellulose degradation activity by binding the cellulosome complex to the cellulose substrate; secondarily, HLDs aid the binding of the CbpA/cellulosome to the C. cellulovorans cell surface.